Analisis Strategi Pemasaran Kerajinan Tangan Berbahan Dasar Bambu Di Desa Loyok Kecamatan Sikur - Baiq Leza Saleha; Taslim Sjah; Muhamad Siddik (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2022)
This study aims to : (1) Analyze the marketing system of bamboo handicrafts currently taking place in Loyok Village, Sikur District; (2) Analyze the right marketing strategy to market bamboo handicraft products in Loyok Village, Sikur District. The research method in this research is descriptive method. Data collection techniques were interview and observation. The unit of analysis in this research is the bamboo handicraft entrepreneur in Loyok Village, Sikur District. Sources of data used were primary and secondary data. The types of data used in this research were qualitative and quantitative data. Analysis applied were is descriptive analysis and SWOT analysis. The results showed that the marketing system carried out by entrepreneurs of woven bamboo crafts in Loyok Village was an indirect marketing system, uses marketing channels or marketing media. The marketing strategy for bamboo handicrafts in Loyok Village is a turn around strategy. This strategy makes use opportunities as well as possible and overcomes the weaknesses of the bamboo craft business. The main strategy is to have a business license and have their own brand, expand the marketing scope of bamboo crafts, and market bamboo crafts online. Keywords: Bamboo, Bamboo Products, Marketing Strategy, SWOT